1992
DOI: 10.1016/0014-5793(92)81212-5
|View full text |Cite
|
Sign up to set email alerts
|

Spleen protein tyrosine kinases TPK‐IIB and CSK display different immunoreactivity and opposite specificities toward c‐src‐derived peptides

Abstract: Polyelonal antibodies have been raised against two synthetic peptide5 reproducing the 48-64 and 353-369 scqaen~s ofCSK, a protein tyrosine kinase implicated in the down-regulation of sre-related protein kinases. Both antibodies specifically recognize recombinant CSK and a CSK-related 49 kDa protein tyrosine kinase pr~ent in spleen but they do not cross-react with purified TPK-nB, a spleen protein tyro~ine kina~ sharing with CSK catalytic activity toward src kina~es and incapability to autophosphorylate. CSK an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…2A) and after conversion to the Fmoc derivative (17) incorporated into the Src autophosphorylation peptide EDNE(F 3 Y)TA by solid phase peptide synthesis. EDNEYTA has previously been reported to be a Csk substrate (18), and we confirmed that here (k cat ϭ 14 Ϯ 0.4 min…”
Section: Resultssupporting
confidence: 79%
“…2A) and after conversion to the Fmoc derivative (17) incorporated into the Src autophosphorylation peptide EDNE(F 3 Y)TA by solid phase peptide synthesis. EDNEYTA has previously been reported to be a Csk substrate (18), and we confirmed that here (k cat ϭ 14 Ϯ 0.4 min…”
Section: Resultssupporting
confidence: 79%
“…The Klngse Assays. Inhibition of substrate phosphorylation by the purified recombinant EGF-R intracellular domain (ICD) (9), v-abl (10), c-src (11), c-lyn (12), c-fgr (13), TPK-IIB (14), cAMP-dependent protein kinase, phosphorylase kinase (15), and casein kinases 1 and-2 (16,17) was assayed as 4escribed.…”
mentioning
confidence: 99%
“…The activity of the other protein-tyrosine kinases was assayed under the same conditions described for c-Fgr, using the following as substrates: 0.1 mM cdc2 peptide for Lyn, Fyn, and Lck, 2 mM angiotensin I1 for Syk, and 0.6 mM C-terminal Src-(514-533)-peptide for CSK. In the latter case, the assay was performed as described by Brunati et al (1992). Tyrosine kinase autophosphorylation activity was assayed at 30°C in the same medium described above, except that the peptide substrate was omitted.…”
Section: Methodsmentioning
confidence: 99%
“…CSK, c-Fgr, Fyn, Syk, and Lyn were purified to near homogeneity from rat spleen as described by Brunati et al (1992Brunati et al ( , 1993Brunati et al ( , 1995b and DonellaDeana et al (1992). Lck (recombinant glutathione S-transferaseLck) was a generous gift of Dr Siegmund Fischer (Paris, France).…”
Section: Methodsmentioning
confidence: 99%